Differential hepatoprotective mechanisms of rutin and quercetin in CCl4-intoxicated BALB/cN mice - Domitrović Robert; Jakovac Hrvoje; Vasiljev Marchesi Vanja; Vladimir-Knežević Sanda; Cvijanović Olga; Tadić Žarko; Romić Željko; Rahelić Dario (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the mechanisms underlying the protective effects of quercetin-rutinoside (rutin) and its aglycone quercetin against CCl4-induced liver damage in mice. Methods: BALB/cN mice were intraperitoneally administered rutin (10, 50, and 150 mg/kg) or quercetin (50 mg/kg) once daily for 5 consecutive days, followed by the intraperitoneal injection of CCl4 in olive oil (2 mL/kg, 10% v/v). The animals were sacrificed 24 h later. Blood was collected for measuring the activities of ALT and AST, and the liver was excised for assessing Cu/Zn superoxide dismutase (SOD) activity, GSH and protein concentrations and also for immunoblotting. Portions of the livers were used for histology and immunohistochemistry. Results: Pretreatment with rutin and, to a lesser extent, with quercetin significantly reduced the activity of plasma transaminases and improved the histological signs of acute liver damage in CCl4-intoxicated mice. Quercetin prevented the decrease in Cu/Zn SOD activity in CCl4-intoxicated mice more potently than rutin. However, it was less effective in the suppression of nitrotyrosine formation. Quercetin and, to a lesser extent, rutin attenuated the inflammation in the liver by down-regulating the CCl4-induced activation of nuclear factor-kappa B (NF-κB), tumor necrosis factor-α (TNF-α) and cyclooxygenase (COX-2). The expression of inducible nitric oxide synthase (iNOS) was more potently suppressed by rutin than by quercetin. Treatment with both flavonoids significantly increased NF-E2-related factor 2 (Nrf2) and heme oxygenase (HO-1) expression in injured livers, although quercetin was less effective than rutin at an equivalent dose. Quercetin more potently suppressed the expression of transforming growth factor-β1 (TGF-β1) than rutin. Conclusion: Rutin exerts stronger protection against nitrosative stress and hepatocellular damage but has weaker antioxidant and anti-inflammatory activities and antifibrotic potential than quercetin, which may be attributed to the presence of a rutinoside moiety in position 3 of the C ring.